2010
DOI: 10.1016/j.molcel.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Pol II CTD Recruits Multiple HDACs, Including Rpd3C(S), for Methylation-Dependent Deacetylation of ORF Nucleosomes

Abstract: Methylation of histone H3 by Set1 and Set2 is required for deacetylation of nucleosomes in coding regions by histone deacetylase complexes (HDACs) Set3C and Rpd3C(S), respectively. We report that Set3C and Rpd3C(S) are co-transcriptionally recruited in the absence of Set1 and Set2, but in a manner stimulated by Pol II CTD kinase Cdk7/Kin28. Consistently, Rpd3C(S) and Set3C interact with Ser5-phosphorylated Pol II and histones in extracts, but only the histone interactions require H3 methylation. Moreover, reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
240
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(262 citation statements)
references
References 52 publications
20
240
2
Order By: Relevance
“…5,14 The association but not hypophosphorylated Pol II, and that the interaction required Kin28, a Ser5 and Ser7 Pol II CTD kinase. 14 Furthermore, in vitro peptide binding assays showed that reconstituted Rpd3C(S) bound strongly to peptides phosphorylated at Ser5, and to di-phosphorylated peptides (Ser2P and Ser5P) even more so, when compared to unmodified peptides or peptides with Ser2 or 5 mutated to aspartic acid.…”
Section: Chromatin Remodeling Complexes Potentially Function Coordinamentioning
confidence: 94%
See 2 more Smart Citations
“…5,14 The association but not hypophosphorylated Pol II, and that the interaction required Kin28, a Ser5 and Ser7 Pol II CTD kinase. 14 Furthermore, in vitro peptide binding assays showed that reconstituted Rpd3C(S) bound strongly to peptides phosphorylated at Ser5, and to di-phosphorylated peptides (Ser2P and Ser5P) even more so, when compared to unmodified peptides or peptides with Ser2 or 5 mutated to aspartic acid.…”
Section: Chromatin Remodeling Complexes Potentially Function Coordinamentioning
confidence: 94%
“…25 Recently, multiple studies have shown that both HATs and HDAs are co-transcriptionally recruited to coding regions. 1,5,8,14,24 The activities of these factors in coding regions have additionally been linked to the facilitation of transcription elongation. For example, acetylation by SAGA (Gcn5) and NuA4 (Esa1) in the GAL1 ORF mediates co-transcriptional histone eviction and Pol II processivity through coding regions.…”
Section: Histone Acetylation Is Inversely Correlated With Histone Occmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitylation of H2B K123 by the Rad6-Bre1 ubiquitin conjugase-ligase proteins in yeast (11-13) is required for dimethylation and trimethylation of H3 K4 and K79 by the Set1/COMPASS and Dot1 methyltransferases, respectively (14-16). Histone H3 K4 dimethylation and trimethylation subsequently stimulate the recruitment and activity of histone acetyltransferase and deacetylase complexes, thereby governing histone acetylation patterns on genes (17)(18)(19)(20).From its position at the top of a histone modification cascade that determines the methylation and acetylation state of active chromatin, H2B monoubiquitylation and the factors that establish this mark are key regulators of gene expression. In addition to Rad6 and Bre1, the conserved Paf1 complex (Paf1C) is required for H2B K123 ubiquitylation.…”
mentioning
confidence: 99%
“…Ubiquitylation of H2B K123 by the Rad6-Bre1 ubiquitin conjugase-ligase proteins in yeast (11-13) is required for dimethylation and trimethylation of H3 K4 and K79 by the Set1/COMPASS and Dot1 methyltransferases, respectively (14-16). Histone H3 K4 dimethylation and trimethylation subsequently stimulate the recruitment and activity of histone acetyltransferase and deacetylase complexes, thereby governing histone acetylation patterns on genes (17)(18)(19)(20).…”
mentioning
confidence: 99%